Evaluating the influence of old and new rental systems on the physical condition of historic mixed-use buildings: a case study of Lebanon - Sedki, Ali (Frontiers in Built Environment, 2023)
This article investigates the link between the physical condition of built heritage and official local authorities’ legislation in Lebanon. The research analyzed the impact of occupation on the physical condition of dwellings under the prevailing official inherited rental legislation, identifying the scale of the problem and the factors leading to it. The responsibilities of the Lebanese official bodies for rental legislation regarding historical buildings were thoroughly discussed. Moreover, a field survey for the condition of historical dwellings was conducted. To accomplish its objectives, the study employed a three-stage methodology. The first stage involved reviewing archival records, current legislation, and relevant literature to gain a comprehensive understanding of historical dwellings laws and regulations in Lebanon. The second stage was divided into two parts. First, the case study area of the Yacob Al Labban historical square in Tripoli, Lebanon, was selected and justified. This area was examined to understand the impact of local authorities’ legislation and rental regulations on the physical condition of its historical dwellings. Second, a field survey was conducted to gather specific information on building typology, physical condition, and building defects. This data will help establish a connection between legislation and buildings’ physical conditions. In the third stage, the findings were analyzed, interpreted, and compared with the existing literature to draw meaningful conclusions about the relationship between legislation and the condition of historical buildings in Lebanon. The research results revealed a strong relationship between the deterioration of historical dwellings and rental legislation. Additionally, the study found that low rental fees were directly associated with a lack of maintenance across all types of rentals.